Letters of Eighteenth-century Court Painters: On the Self-awareness and Status of the Artist - Balaišytė, Lina (Senoji Lietuvos literatūra, 2014)
The paper analyses the letters of two painters – Stefan Cybulski and Johann Sebastian Dür, who worked in the court of Hieronim Florian Radziwiłł – to their master. The artists’ correspondence – which lasted for many years – is a rare historical source which shows how artists were appreciated in the eighteenth century and the nature of their own self-awareness. The personal experiences in the court of a noble of the Grand Duchy of Lithuania that the artists describe in their letters reveal the nature of the relations between the artist and the noble, and the artist’s place in the hierarchy of a noble’s court. The historiography presents the biography of Cybulski, who was kept a prisoner in the court for his escape, as an example of the fate of an unhappy artist in the court of a ruthless magnate. Meanwhile, the arrested artist lived a life that was quite ordinary for a court servant: he carried out his master’s commissions, had students, and even married. In his letters the artist reminded his master of the losses he had incurred due to his imprisonment and would ask him to redress the grievance. Cibulsky’s pleading letters, characterized by their original rhetoric and emotional narrative, offered a hyperbolized picture of the painter’s hardships, although it must be admitted that while working for Hieronim Florian, and later for other members of the Radziwiłł family, Cibulsky grew fairly rich. The relations between the noble and the artist were formed in accordance with the ordinary patterns of courtly life based on the subordination and loyalty of the servant to the master, and on the obligation of the master to protect his subject and take care of his family. In their letters both artists did their best to demonstrate their ultimate humility, vouchsafing of their loyalty to their master and of their diligent work for his benefit. Servants perceived the mastering of their craft and paying good service to their lord as their duty. They asked their master for protection against the city’s claims, the lootings of the army and the lawlessness of the court officials. The letters of Dür, who came from Switzerland, demonstrate a greater experience of individualism that was characteristic of artists from abroad. The painter opposed the established hierarchy and found it unacceptable to be treated as a person of a lower status in the court.